An investigation of record linkage refusal and its implications for empirical research - Arne Jonas Warnke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Linking survey data to administrative records provides access to large quantities of information such as full employment biographies. Although this practice is becoming increasingly common, only a small number of studies in the field of social sciences have thus far investigated the variables associated with linkage consent. These studies have produced diverging results with regard to the relevance of certain characteristics for the provision or non-provision of linkage consent. In this study, we analyze two comparable German datasets, thereby shedding new light on the possible reasons for previously inconsistent results. This is also the first study in which possible linkage consent bias is investigated in applied models, via the replication of an existing study for the sample in which respondents did not consent to data linkage. Whilst similar results are found between standard sociodemographic variables and linkage consent, there are considerable inconsistencies between the comparable datasets in terms of variables such as individual personality traits and work satisfaction. Overall, however, the results are promising - results do not differ much where respondents who did not provide linkage consent are considered.
urn:nbn:de:bsz:180-madoc-434756
Keywords: C18; C83; 330; Linkage Consent; Consent Bias; Administrative Records; Record Linkage; Linked-Employer-Employee Data; Survey Data; Selection Bias